2022
DOI: 10.3389/fmars.2022.946824
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of warm advection on the southward expansion of sea ice during early winter in the Bering Sea

Abstract: Recent observations demonstrate that the Bering Sea exhibits a substantial positive trend of sea ice area increment (ΔSIA, difference in SIA between the current and preceding months) in January contrasted to the considerable negative sea ice area (SIA) trend from 1979 to 2020, and the ΔSIA is unrelated to the local wind field anomaly. To better understand the January ΔSIA variability and its physical characteristics, we explore two distinct empirical orthogonal function (EOF) modes of sea ice concentration inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The merged sea level anomaly (SLA) at a spatial resolution of 1/4 degree and a time resolution of 1 day (ftp://ftp.aviso.oceanobs.com/global/) and ocean surface current analysis data (http://www.oscar.naaa.gov) at 5‐day intervals and 1 × 1 spatial resolution were extracted to identify the main currents and mesoscale eddies. Wind stress curl and Ekman pumping velocity (EPV) based on ASCAT wind vectors were coagulated according to Stewart (2004) and Wang, Su, et al (2022); Wang, Wei, et al (2022). The gridded averaged wind at 10 m above mean sea level was retrieved from the ASCAT scatterometer onboard the Metop satellites, and had spatial resolutions of 0.25° in longitude and latitude (ftp://ftp.ifremer.fr/ifremer/cersat).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The merged sea level anomaly (SLA) at a spatial resolution of 1/4 degree and a time resolution of 1 day (ftp://ftp.aviso.oceanobs.com/global/) and ocean surface current analysis data (http://www.oscar.naaa.gov) at 5‐day intervals and 1 × 1 spatial resolution were extracted to identify the main currents and mesoscale eddies. Wind stress curl and Ekman pumping velocity (EPV) based on ASCAT wind vectors were coagulated according to Stewart (2004) and Wang, Su, et al (2022); Wang, Wei, et al (2022). The gridded averaged wind at 10 m above mean sea level was retrieved from the ASCAT scatterometer onboard the Metop satellites, and had spatial resolutions of 0.25° in longitude and latitude (ftp://ftp.ifremer.fr/ifremer/cersat).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have inferred that future warmer ocean conditions may lead to elevated biomass in regions that were already dominated by picophytoplankton (Flombaum et al, 2020). A high Pro abundance has been reported along with various strains and genomes in the tropical western Pacific (Biller et al, 2014;Kelly et al, 2012;Wang, Su, et al, 2022;Wang, Wei, et al, 2022). With global warming, the Pro abundance may increase by 29% by the end of this century, and its distribution trend may expand to the north and south poles (Flombaum et al, 2013(Flombaum et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods fall short of providing insights into the underlying process of SST changes. The most significant impact of air-sea heat flux on SST occurs in November [44], making it challenging to directly depict the heat transfer carried by Pacific inflow on the local SST at a monthly time scale. To overcome this limitation, we adopted a daily time scale and calculated the daily spatial average of the SST.…”
Section: Warm and Cold Eventsmentioning
confidence: 99%
“…The changes in sea ice in the Bering Sea are influenced by several factors, including large-scale circulation [32][33][34], cyclone activity [33,35,36], wind anomalies [32,33,[37][38][39], southward input of sea ice from the Bering Strait [40], SST, and warm water inflow from the Pacific Ocean [4,[41][42][43][44]. While previous studies have focused on winter sea ice in the Bering Sea and its interannual changes, early sea ice has rarely been explored [29].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely believed that the Bering Sea shelf current is weak and has far less significant effects on sea ice than the anomalous wind field (Niebauer et al., 1999; Rodionov et al., 2005; Stabeno et al., 2001). However, recent studies have shown that the December SIA is closely related to the wind‐driven northward heat transport in November (Wang et al., 2023a), and the SIA increment in January is mainly modulated by the ocean forcing in December (Wang et al., 2022). The impact of ocean forcing on sea ice may be more pronounced than anticipated.…”
Section: Introductionmentioning
confidence: 99%